Perlindungan Hukum Terhadap Anak Yang Berkonflik Dengan Hukum - Nurillah, Isma; Arista, Windi; Indriani, Santi; Vitriana, Novita (Lex Librum : Jurnal Ilmu Hukum, 2023)
Abstract Children who are in conflict with the law in the process often get pressure so that it affects their physical and psychological conditions. Whereas the child has the right to receive social rehabilitation and social reintegration and has also been regulated in the Regulation of the Minister of Social Affairs of the Republic of Indonesia No. 26 of 2018 concerning Social Rehabilitation and Social Reintegration for Children in Conflict with the Law. In addition, in the juvenile criminal justice process, children's rights must be protected at every stage, as a form of respect for children's human rights. The formulation of the problem in this study is how the form of legal protection for children in conflict with the law in the juvenile criminal justice system and how the application of diversion to children in conflict with the law in the criminal justice system. This study uses a normative juridical method that focuses on literature studies. The results of the study state that in the criminal justice process, children must prioritize children's rights, and must get protection from every stage as a form of respect for children's human rights which are applied in the Juvenile Justice System Act with the concept of diversion. Keywords: children in conflict with the law; juvenile criminal justice process; diversion; children's rights